2016
DOI: 10.3762/bjoc.12.88
|View full text |Cite
|
Sign up to set email alerts
|

Separation and identification of indene–C70 bisadduct isomers

Abstract: SummaryFollowing an initial work on the isolation of a single geometric isomer from an indene–C70 bisadduct (IC70BA) mixture, we report the full fractionation and identification of the bisadduct species in the material. Eleven fractions of IC70BA isomers were separated by high-performance liquid chromatography. A number of fractions contained relatively pure isomer species and their configuration were deduced using a variety of analytical techniques including 1H and 13C NMR and UV–vis spectroscopy. The electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…Variability of the π‐system topology in the trifluoromethylated isomers is reflected in the electronic absorption spectra, and the characteristic spectral features can be of assistance in the task of structural identification. More, importantly, the UV/Vis spectroscopic properties are of key significance with regard to optoelectronic applications . The spectra of the individual C 70 (CF 3 ) n compounds considered in the present study are shown in Figures S9–S13 in the Supporting Information.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Variability of the π‐system topology in the trifluoromethylated isomers is reflected in the electronic absorption spectra, and the characteristic spectral features can be of assistance in the task of structural identification. More, importantly, the UV/Vis spectroscopic properties are of key significance with regard to optoelectronic applications . The spectra of the individual C 70 (CF 3 ) n compounds considered in the present study are shown in Figures S9–S13 in the Supporting Information.…”
Section: Resultssupporting
confidence: 85%
“…More, importantly,t he UV/Vis spectroscopic properties are of key significance with regard to optoelectronic applications. [12,[45][46][47][48][49][50] The spectra of the individual C 70 (CF 3 ) n compounds considered in the presents tudy are showni nF iguresS9-S13 in the Supporting Information. Except for the isomers 12-I and 12-II,t he spectra of which coincide with those previously reported, [11,12] the spectroscopic data are reported for the first time.…”
Section: Uv/vis Spectroscopy and Band Gapsmentioning
confidence: 99%
“…[35][36][37] Isolated single IC70BA isomers have been shown to alter the device PCE. [38] However, there is little information on how a mixture of regio-isomers affects the device output. To address this point, we produced a number of standard architecture PSCs (Figure 1d and 1e) using processing conditions tailored for a IC70BA sample with a fixed regio-isomeric distribution (hereafter IC70BA#1), and then transferred this knowledge to another IC70BA sample (hereafter IC70BA#2) exhibiting a dissimilar regio-isomeric distribution, in order to investigate the importance of the regio-isomerism on the vertical phase separation of the P3HT:IC70BA BHJ.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the C 60 bisadducts were more deeply studied. Comparative studies on OSCs utilizing the purified C 70 bisadducts have appeared very recently. To study a relation between anisotropy and OSC efficacies in the present work, we have calculated anisotropies of polarizability of the C 70 derivatives tested in the above-cited works and collated the computational results with the corresponding PCE measurements.…”
Section: Introductionmentioning
confidence: 99%